Pharmaceutical Standardization of a Novel Anti Leukemic Ayurvedic Herbomineral Formulation - Vinamra Sharma, Dr (International Journal of Pharmaceutical & Biological Archive, 2015)
Pharmaceutical Standardization of a Novel Anti Leukemic Ayurvedic Herbomineral Formulation